DESAIN WEBSITE TOKO HONDA RADJA MOTOR DALAM KONSEP PENJUALAN ONLINE - Khairul Anwar, Drs. Suib awrus, M.PD, Drs. Syafei, M.Ag (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Purpose of this final work is (1) Produce a concept design of the website design online sales, (2) Produce a website design visualization products for sale at a car parts store, and (3) Communicating the website design as an alternative to the place of purchase in accordance with the needs of consumers. Sources of this thesis is the method of data collection in the form of field observations, interviews, as well as through the documentation on the store Honda Radja Motor. Final work in the form of web design for the communicative and persuasive sales promotion Honda Radja Motor shop in which there is information and sales of Honda car spare part with drawings, color, typography, and layout are interesting. Keyword: Design, Website, Shop, Honda Radja Motor